Prognostic Factors and Metastatic Patterns in Primary Myxoid/Round-Cell Liposarcoma. (28th November 2011) - Haniball, J.; Sumathi, V. P.; Kindblom, L.-G.; Abudu, A.; Carter, S. R.; Tillman, R. M.; Jeys, L.; Spooner, D.; Peake, D.; Grimer, R. J.
Abstract : Background . This study aimed to investigate prognostic factors for patients with myxoid/round-cell liposarcoma (MRCLS), in particular the significance of the round cell component, and to identify metastatic patterns as well as possibly suggest a suitable strategy for followup. Methods . Clinical, morphologic, and follow-up data from 160 patients with MRCLS was reviewed and statistically analysed. Results . Of 130 tumours with the round cell component evaluated, 61 had no round cell component, 27 had <5% round cell component, and 42 had >5%. All patients underwent surgical excision, 15 requiring amputation. 107 patients received adjuvant radiotherapy. Local recurrence occurred in 19 patients (12%), predominantly in patients with marginal or intralesional margins and a round cell component. Overall disease specific survival was 75% at 5 years and 56% at 10 years and was related to the proportion of round cell component. Of 52 patients who developed metastases, 38 (73%) had purely extrapulmonary metastases. We could not identify any factors predicting the site of metastases developing. Conclusions . The occurrence of any round cell component is the most important adverse prognostic factor for patients with MRCLS; patients with >5% round cell component are at higher risk of local recurrence, metastasis and tumour-related death and should be considered for adjuvant radiotherapy and possibly chemotherapy. The best method of monitoring extrapulmonary metastases remains to be established.